2001
DOI: 10.1159/000048626
|View full text |Cite
|
Sign up to set email alerts
|

Negligible Effects of Depression on Verbal and Spatial Performance in Alzheimer’s Disease

Abstract: We examined whether a diagnosis of depression affects verbal and visuospatial performance in Alzheimer’s disease (AD). Using data from a population-based study, persons with AD and depression (AD/D), AD alone and a control group of normal older adults were compared in two tests of verbal ability (category and letter fluency) and two tests of visuospatial skill (block design and clock drawing). As expected, there were clear AD-related deficits across all cognitive tasks. More importantly, the AD and AD/D groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…No significant relationships were observed between numbers of mood symptoms and scores on neuropsychological tests. Consistent with earlier studies there was no significant correlation between a general measure of depression and specific neuropsychological tests performance (Kuzis et al, 1999, Berger et al, 2002.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No significant relationships were observed between numbers of mood symptoms and scores on neuropsychological tests. Consistent with earlier studies there was no significant correlation between a general measure of depression and specific neuropsychological tests performance (Kuzis et al, 1999, Berger et al, 2002.…”
Section: Discussionsupporting
confidence: 90%
“…Kuzis et al (1999) reported that depressed and non-depressed patients with dementia were comparable in memory and executive functions. It has also been observed that AD-patients with and without depression had similar scores on tests of verbal and spatial performance (Berger et al, 2002). As subgroups were rather small, false negative results cannot be excluded in this study.…”
Section: Introductionmentioning
confidence: 53%
“…More recently, Berger et al 27 reported that AD and AD plus depression patients were indistinguishable on a series of cognitive tasks, including clock drawing. As for schizophrenia, similarly, although it has been suggested 28,29 that elderly schizophrenia and AD patients perform at similar lower levels on CDTs, the specific task items that may help differentiate these morbid conditions are still controversial.…”
mentioning
confidence: 99%
“…[4][5][6] Depression is associated with widespread cognitive deficits. 10 Several cross-sectional studies [11][12][13] have found that AD subjects with and without depression were indistinguishable on cognitive test performance. Although some researchers have reported that memory and executive functioning are most affected by depression among elderly patients, 9 other researchers have reported subtle difficulties across most cognitive tests, rather than significant difficulties in one or two specific cognitive domains.…”
mentioning
confidence: 99%